Knowledge Management and Acquisition for Intelligent Systems 14th Pacific Rim Knowledge Acquisition Workshop, PKAW 2016, Phuket, Thailand, August 22-23, 2016, Proceedings - Ohwada, Hayato; Yoshida, Kenichi (Lecture Notes in Artificial Intelligence, 2016)
This book constitutes the proceedings of the 14th International Workshop on Knowledge Management and Acquisition for Intelligent Systems, PKAW 2016, held in Phuket, Thailand, in August 2016. The 16 full papers and 5 short papers included in this volume were carefully reviewed and selected from 61 initial submissions. They deal with knowledge acquisition and machine learning; knowledge acquisition and natural language processing; knowledge acquisition from network and big data; and knowledge acquisition and applications.